On a Conjecture of Zheng Jianhua - Wu, Zhaojun (Sarajevo Journal of Mathematics, 2024)
In this paper, a new proof of the existence of the $T$ direction is given. Furthermore, we prove that for a meromorphic function $f$ with finite lower order, satisfying $\limsup\limits_{r→ ∞} \frac{T(r,f)}{\log^{2}r}=∞,$ there exists a $T$ direction concerning small functions. 1991 Mathematics Subject Classification. Primary 30D30, Secondary 30D35